Early appearance of the retinal tapetum, cones, and rods in the larvae of the African catfish Clarias gariepinus - Gunzo Kawamura; Teodora Bagarinao; Joanevieve Justin; Chiau Yu Chen; Leong Seng Lim (2016)
In the retina of the African catfish Clarias gariepinus, the pigment epithelium and the tapetum were formed in newly hatched larvae, the cones developed within 2 days, and the rods within 3 days after hatching. The retinal tapetum shone under surface light under a light microscope; the shine was located in the apical projections of the pigment epithelial cells. Early appearance of the retinal elements enables African catfish larvae to see and feed well even in dim light.